Method of connection establishment between CPE and the cloud platform - UFengchao FU; Yuanbao XIE (Dianxin kexue)
SDN and NFV technology have aroused more and more attention. The main idea of vCPE is to split the CPE into two parts and to make the L3 functions up to the network. Through this method, CPE can be simplified and the difficulty for subscribers to operate and maintain CPE can be reduced. For operators, vCPE can reduce the probability of on-site service, and can provide value-added services for subscribers. The problem of connection between the CPE and the cloud platform was studied. By using VxLAN and NvGRE, the L2 connection between CPE and cloud platform could be established, and at the same time, the change to existing huge CPEs was small.